1980
DOI: 10.3758/bf03209745
|View full text |Cite
|
Sign up to set email alerts
|

The effects of social isolation on two shock-induced aggressive responses in rats

Abstract: This experiment investigated the effects of social isolation during development and during adulthood on the topography of the shock-induced aggressive behavior of rats. Rats isolated during development from weaning to adulthood displayed more shock-induced biting than rats housed in groups during that period. Isolation during development did not affect the frequency of the upright boxing behavior, but isolation during adulthood reduced the frequency of the boxing response regardless of rearing conditions durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
9
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
(28 reference statements)
3
9
0
Order By: Relevance
“…In apparent contrast to the foregoing results, 5 studies of SIF have reported that rats isolated from weaning to testing at 90 or 110 days of age boxed less on the first SIF session than did socially reared animals (Hutchinson et al, 1965;Creer & Powell, 1971;Hutzell & Knutson, 1972;Thor & Ghiselli, 1974;Knutson & Kane, 1980). Knutson and Kane (1980) have found, however, that isolated rats which were regrouped between 90 and 110 days fought substantially more than continuously isolated animals and slightly more than continuously group-housed animals. Furthermore, Knutson and his colleagues have found that isolation with or without regrouping increases the frequency or severity of biting in response to shock (Hutzell & Knutson, 1972;Knutson & Kane, 1980).…”
mentioning
confidence: 59%
“…In apparent contrast to the foregoing results, 5 studies of SIF have reported that rats isolated from weaning to testing at 90 or 110 days of age boxed less on the first SIF session than did socially reared animals (Hutchinson et al, 1965;Creer & Powell, 1971;Hutzell & Knutson, 1972;Thor & Ghiselli, 1974;Knutson & Kane, 1980). Knutson and Kane (1980) have found, however, that isolated rats which were regrouped between 90 and 110 days fought substantially more than continuously isolated animals and slightly more than continuously group-housed animals. Furthermore, Knutson and his colleagues have found that isolation with or without regrouping increases the frequency or severity of biting in response to shock (Hutzell & Knutson, 1972;Knutson & Kane, 1980).…”
mentioning
confidence: 59%
“…These behaviors are known to change in both quality and quantity during the course of development of the animals (Pellis & Pellis, 1987, 1998. The stage of sexual maturity is especially considered an important turning point (Knutson & Kane, 1980;Meaney & Stewart, 1981;Panksepp, 1981;Pellis & Pellis, 1987. Then, it is likely that the degree or the direction the effect of isolation has during the postweaning stage also may differ from that during the postmaturity stage.…”
mentioning
confidence: 99%
“…One of the interesting aspects of the effects of isolation on behavior is the inconsistency to be found in the aggression literature. While some studies of resident-intruder aggression indicate that isolation results in more aggressive responding (e.g., Flannelly & Thor, 1976;Luciano & Lore, 1975), studies of shock-induced aggression suggest that less aggression can be associated with isolation housing (e.g., Hutzell & Knutson, 1972;Knutson & Kane, 1980). Because different paradigms are used, it is possible that the inconsistencies reflect different kinds of aggression (cf.…”
mentioning
confidence: 91%
“…Isolation-rearing and housing is also an independent variable that has been investigated widely in behavioral and physiological studies. In addition to affecting gonadal and adrenocortical functions of rats (e.g., Brain & Nowell, 1971;Dessi-Fulgheri, Lupo di Prisco, & Verdarelli, 1975;Goldsmith, Brain, & Benton, 1976), isolation has been shown to influence such behaviors as habituation (e.g., Einon, Morgan, & Kibbler, 1978), irritability in septal-lesioned animals (Ahmad & Harvey, 1968), and aggression (e.g., Adams, 1976;Flannelly & Thor, 1976;Hutzell & Knutson, 1972;Knutson & Kane, 1980;Luciano & Lore, 1975). One of the interesting aspects of the effects of isolation on behavior is the inconsistency to be found in the aggression literature.…”
mentioning
confidence: 99%